2017
DOI: 10.1039/c7tb02436c
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity and osseointegration of silver-coated poly(ether ether ketone) prepared using the polydopamine-assisted deposition technique

Abstract: PEEK-PDA-Ag substrates may be a promising orthopaedic implant material due to the outstanding biocompatibility and antibacterial properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 68 publications
0
43
0
Order By: Relevance
“…Recently, multiple PEEK modification studies have been conducted to improve the osseointegration between implants and bone tissue [ [10] , [11] , [12] ]. Three main strategies has been studied to overcome the bio-inert character of PEEK, including surface modification with either physical or chemical methods, preparation of functional PEEK composites by blending bioactive materials and designing three dimensional porous PEEK materials [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, multiple PEEK modification studies have been conducted to improve the osseointegration between implants and bone tissue [ [10] , [11] , [12] ]. Three main strategies has been studied to overcome the bio-inert character of PEEK, including surface modification with either physical or chemical methods, preparation of functional PEEK composites by blending bioactive materials and designing three dimensional porous PEEK materials [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Being able to award the biosubstitutes multiple functions to meet the requirements of tissue regeneration, surface modification of orthopaedic implants has evolved into an essential and promising technology. For example, the osseointegration and antimicrobial properties of orthopaedic implants can be significantly improved on appropriate surface modification [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…26,27 In a similar manner to prophylactic antibiotic use, Gao et al demonstrated that the majority of silver from 70 nm AgNP on the surface of a PEEK implant were released within 24 hours, yielding a 5 lg/mL extract; the cumulative silver release curve plateaued after 5 days. 28 A reduction in viability of MC3T3-E1 osteoblast precursor cells was observed, but this difference versus the control was eliminated by day 5 due to dilution of the silver with repeated media changes. Implantation of this material into rats demonstrated antimicrobial activity and was observed to osseointegrate similar to the materials without AgNP after 2 weeks of implantation.…”
Section: Discussionmentioning
confidence: 99%